Avaliação da atividade antioxidante e dos mecanismos envolvidos no efeito antinociceptivo e anti-inflamatório do 2-alilfenol - Assis, Davidson Barbosa (2022)
2-Allylphenol (2-AP) is a phenylpropanoid widely marketed in China under the name Yinguo. Extracted from the exosperm of the Ginkgo biloba fruit, 2-AP has previously reported antibacterial, antitumor, antifungal and antinociceptive activities. However, it is necessary to elucidate in more detail the mechanism by which 2-AP promotes its antinociceptive effect, by in silico, in vivo and in vitro methodologies. 2-AP was purchased from SIGMA (St. Louis, MO, USA) and administration was carried out at doses of 50, 75 and 100 mg/kg (i.p.) always thirty minutes before the performance of pharmacological tests. All experimental procedures were previously approved by the CEUA - UFPB's Committee on Ethics in the Use of Animals -, under certificate no. 4443051018. The experiments started with the investigation of the antinociceptive mechanism of 2-AP. To study the participation of the nitroxidergic, GABAergic and dopaminergic systems, respectively, L-NNA, flumazenil and sulpiride were administered fifteen minutes before the treatment with 2-AP in the test of abdominal writhing induced by acetic acid. In order to increase the evidence of the action of 2-AP in the adenosinergic pathway, previously reported, a study of molecular docking was carried out. The carrageenan-induced peritonitis test was used to assess the anti-inflammatory effect of 2-AP by evaluating cell migration and levels of pro-inflammatory cytokines TNF-α and IL-1β in peritoneal fluid. Finally, the antioxidant activity of 2-AP was determined by tests of total antioxidant capacity, DPPH scavenging activity, hydroxyl radical scavenging activity test, superoxide scavenging activity test. Treatment with LNNA, flumazenil and sulpiride did not reverse the antinociceptive effect of 2-AP, ruling out the participation of the nitroxidergic, GABAergic and dopaminergic systems in the antinociceptive effect. Docking studies confirmed an affinity between 2-AP and the A2a receptor, this interaction may be related to the reduction in the production of pro-inflammatory cytokines. In anti-inflammatory tests, 2-AP inhibited leukocyte migration via reduced levels of TNF-α and IL-1β in the peritonitis test. It presented a high total antioxidant capacity, this activity being provided through the scavenging of superoxide radicals, demonstrating that its antioxidant activity may also be helping in the anti-inflammatory and antinociceptive effect. In view of the results, the clinical potential of 2-AP for the treatment of pain and inflammation becomes evident.